Art and video games: what state is it in? - González-Sancho, Roy (2025)
The arts have varied in its composition and members during the last 100 years. In this way from music, architecture, dance, painting, poetry and sculpture, cinema was incorporated involved in a controversy about its originality or possibilities to develop its own language. In this context, hand in hand with the emergence of Information and Communication Technologies, video games joined into this controversy, with criticisms and accusations that showed parallels spaces with the situation reported by cinematography in its time. Therefore, the general aim of this paper is to analyze the development of the discussion in specialized and academic media about the status of video games as an art form or means of its expression. Among the results, there are extensive statements, works and theoretical developments that manage to justify the artistic status of video games or at least their consideration as a field of artistic expression, which has managed to develop its own language, with a particular aesthetic characterized by the participation and interactivity of the person involved in its use, different from the contemplative experience of the traditional arts.